Implementation of a Comprehensive Eco-Riparian Concept to Landscape Design of Water Source Area in Macari Village, Batu City - Angga Perdana (Jurnal Ilmu Lingkungan, 2024)
The eco-riparian concept application on the riverside is one of the programs of the Ministry of Environment and Forestry of the Republic of Indonesia. The water source in Macari Village is one of the suppliers of raw water discharge in the Brantas watershed. Residential and industrial areas currently surround Macari Village Water sources, so it decreases the water quality, and pollution is often found due to industrial and household waste contamination. This research aims to find comprehensive eco-riparian concept design solutions to conserve water resources. By using a combined methodology between case studies and literature reviews, comprehensive eco-reparation design criteria were found, such as wetland restoration by using the terraced pond, vegetation management of the water bodies, ground covers, cliff retaining, aesthetic support vegetation, wastewater management, and drainage plans so it will not pollute the water sources. The development to support the area's vision is manifested in architectural design with ecological and historical characteristics. This design criteria is translated into a holistic visualization of the area to produce a coherent, functional, and aesthetic design. With the design result, all regional development visions are expected to be realized at the location.